Small vices - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Spenser novel, 1997)
In Boston, a girl student is murdered and police arrest a black man who has a history of sexual assault. The prosecution has no problem obtaining a conviction, even though the man is not guilty. PI Spenser is hired to find the man who is.